DEMAND DRIVERS OF FEMALE LABOR FORCE PARTICIPATION: EVIDENCE FROM SELECTED AFRICAN COUNTRIES - O. Idowu, Omowumi (ECONOMICS - INNOVATIVE AND ECONOMICS RESEARCH JOURNAL, 2019)
This study investigates the demand drivers of female labor participation in a panel of twenty (20) selected African countries across five sub-regional groupings (West Africa, East Africa, North Africa, Central Africa and South Africa), over the period 1990-2015. The study sourced data from World Bank Data Bank. Poverty and gender inequality in employment were used and measured respectively by life expectancy at birth and gender ratio in labor participation. Other variables included are wage rates, female marginal labor productivity and household income. Autoregressive Distributive Lags (ARDL) procedure of dynamic panel model was used. The result from the Dynamic Fixed Eﬀect (DFE) revealed that female marginal productivity of labor and gender inequality in employment have a significant positive impact on demand for female labor in the long run, however female marginal productivity was found negative in the short run. It is therefore important that, in order to bridge the gender gap in employment, government should ensure gender sensitive policies and remove all forms of institutional barriers to female labor demand. Eﬀorts should also be made to improve female productivity through training, literacy and household food security. In order for female demand to meet desired response, adequate support services and provisions that can entice female to work outside home should be provided.